Dampak Pembangunan Instalasi Pengolahan Air Limbah Losari di Kota Makassar - Muh Nur Alfaridzi; Burhanuddin Badrun; Suryani Syahrir (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Wastewater Treatment Plant is a structure designed to remove biological and chemical waste from water so that the water is not harmful and can be reused in other activities. So the impact of the construction of the Losari Wastewater Treatment Plant for the surrounding community needs to be known and how effective the use of Moving Bed Biofilm Reactor technology is in processing liquid waste into clean water. This study uses a descriptive research type with a quantitative approach by collecting primary and secondary data taken directly in the field and related agencies. The methods in this study include conducting observations, interviews. However, in this study only two sub-districts were studied, namely Tamalate and Ujung Pandang Districts. So from the results of interviews with agencies and residents affected in the two sub-districts, it shows that the impact of the construction of wastewater treatment plants can reduce the risk of spreading disease and is also able to change household wastewater, bathroom waste, kitchen waste and waste from restaurants into clean water, namely for watering plants around the Losari IPAL area and is suitable for disposal in canals/channels. The results of wastewater processing using Moving Bed Biofilm Reactor technology show quite effective results, namely reducing pH between 6-9 = 7, BOD = from 20 to 4, TSS = from 18 to 12, Ammonia = from 0.53 to 0.24 ppm.